The phylogeography and incidence of multi-drug resistant typhoid fever in sub-Saharan Africa. Issue 1 (December 2018) - Park, Se; Pham, Duy; Boinett, Christine; Wong, Vanessa; Pak, Gi; Panzner, Ursula; Espinoza, Ligia; Kalckreuth, Vera; Im, Justin; Schütt-Gerowitt, Heidi; Crump, John; Breiman, Robert; et al.
Abstract There is paucity of data regarding the geographical distribution, incidence, and phylogenetics of multi-drug resistant (MDR)Salmonella Typhi in sub-Saharan Africa. Here we present a phylogenetic reconstruction of whole genome sequenced 249 contemporaneousS . Typhi isolated between 2008-2015 in 11 sub-Saharan African countries, in context of the 2, 057 globalS . Typhi genomic framework. Despite the broad genetic diversity, the majority of organisms (225/249; 90%) belong to only three genotypes, 4.3.1 (H58) (99/249; 40%), 3.1.1 (97/249; 39%), and 2.3.2 (29/249; 12%). Genotypes 4.3.1 and 3.1.1 are confined within East and West Africa, respectively. MDR phenotype is found in over 50% of organisms restricted within these dominant genotypes. High incidences of MDRS . Typhi are calculated in locations with a high burden of typhoid, specifically in children aged <15 years. Antimicrobial stewardship, MDR surveillance, and the introduction of typhoid conjugate vaccines will be critical for the control of MDR typhoid in Africa. Typhoid fever is caused by the bacteriumSalmonella Typhi. Here, Park et al. analyse the genomes of 249S . Typhi isolates from 11 sub-Saharan African countries, identifying genes and plasmids associated with antibiotic resistance and showing that multi-drug resistance is highly pervasive in sub-Saharan Africa.